The social coinonial construction of pastoral therapy in clergy training - Joubert, Bunyan Fouche (University of the Free State, 2000)
This thesis participated in the negotiation of a shift from modernism to postmodernism concerning pastoral therapy and the training of pastoral therapy. This shift, as it is reflected in social construction theory, poses new challenges to the idea of pastoral therapy, what it is, and especially to training in pastoral therapy. Pastoral therapy is eo-constructed in training according to a postmodern social construction discourse so that it remains intelligible and adaptable within a modernist theological framework. Multiple reflexive conversations were used as a basis of research, resulting in reflexivity and selfreflexivity, engaging trainer, trainees and clients in the social coinoinial (within a specific community) construction of pastoral therapy and pastoral therapy training. Simultaneously they participate in reflecting on the constructing process. As researcher I did not enter the research as a clean slate. Discourses that have shaped me such as culture, theology, family of origin and previous training are considered and presented in an alternative column next to the main discussion as an inner dialogue or autobiographical reflection. Various "worlds" are brought together in this study, namely that of social construction, practical theology, social sciences, family therapy, pastoral work, and pedagogy. Through a social coinonial construction process pastoral therapy is positioned within practical theology. Tangent planes with discourses in social sciences, family therapy, pastoral work and pedagogy are discussed. Multiple reflexive conversations within a two year Masters programme as well as a two year continuing education programme were used to construct pastoral therapy and pastoral therapy training during the research process. Reading material on the different "worlds" and discourses, interviews, discussions, pastoral therapy processes, as well as family-of-origin work are described as core training practices.
Thesis (Ph.D. (Diaconiology))--University of the Free State, 2000
Keywords: Pastoral counseling; Clergy -- Training of